Application of Order Tracking Analysis Method in Fault Diagnosis of Swing Fatigue Tests of Precision Reducers for Robots - Lin Mengxiong; Zhang Xianghui; Yao Liangbo; Gong Yu; Zhang Jingcai; Yang Yikun (Jixie chuandong)
The fatigue life testing of the precision reducer for industrial robots using the reciprocating swing method can better represent the damage of the reducer in actual work. However, during the reciprocating swing testing, the speed and its direction of the reducer are changing. Therefore, it is difficult to locate the fault source of the reducer by performing spectrum analysis on time domain vibration signal to locate the fault point. Thus, an order tracking analysis method is proposed. By re-sampling the non-stationary vibration signals collected during the reciprocating swing fatigue testing of the planetary cycloid reducer for the robot, the stable angle domain signal of the vibration signal is obtained by equal-angle resampling. The order analysis diagram of the vibration signal is obtained by fast Fourier transform of the stationary signal in the angle domain. At the same time, the order characteristics of the planetary gear, cycloid gear, crankshaft, needle roller and crank bearing of the reducer are analyzed. By establishing the relationship between the order analysis result of the vibration signal of the reducer and the characteristic order of each key component, the fault diagnosis of the planetary cycloid reducer under variable speed experimental conditions is realized. The results show that the order tracking analysis method can help locate the faults under time-varying conditions, and provide guidance and assistance for the rapid location of the failure of the swing fatigue experiment.